Immigrants and Religion - Carmel U. Chiswick (Institute for the Study of Labor (IZA), 2014)
Religious considerations affect the decision to immigrate as well as the choice of destination country, and religious behaviors change as immigrants adjust to the economic context of their new country. This paper considers the interaction between the Economics of Religion and the Economics of Immigration, and distinguishes between religiosity per se and an immigrant's religious identity (affiliation). Religious groups are described as quasi-enclaves and immigrant churches as a subset of these. Rising full prices (wage rates) and incomes during the adjustment process affect the religious behavior of immigrants. Religious institutions (referred to as churches) also respond to systematic changes in the religious behaviors of their members.
Keywords: Z12; J61; J11; J15; 330; international migration; immigrant adjustment; quasi-enclave; immigrant church; religiosity; religion; social change